Changes in the amino acid composition depending on the pre-sowing treatment of seeds - Podlasova E.Yu.; Lebedev S.V. (E3S Web of Conferences, 2021)
The use of green mass of annual leguminous crops allows to get a rich amount of protein feed. Therefore, the quality of the green mass must be ensured in the context of sustainable crop production and feed efficiency. Apparently, the use of pre-sowing seed treatment with different-sized metal particles and growth regulators can affect the amino acid composition of crops. In the conducted work, it was found that pre-sowing treatment of seeds with UFP MoO2 increased the content of essential amino acids in peas - 5.75%, millet - 3.61, and in barley with UFP SiO2 - 4.01%. Similarly, UFP MoO2 stimulated the content of proline in the biomass of peas-1.82%, millet-0.15%, barley-0.32% compared to the control.In mixed crops of peas, millet, and barley, the content of leucine-isoleucine increased by -0.36%, lysine-0.13%, tyrosine - 0.04%, proline - 0.76%, threonine-0.36%, alanine - 0.27%, histidine - 0.02%, and glycine - 0.25% compared to the control. The amount of essential amino acids in the mixed crop under the action of the UFP MoO2 increased by 1.38%.